Knowledge and perceptions about generic drugs by users of PSF in triple borders - Laiz Mangini Cicchelero; Ana Paula Contiero Toninato; Rosane Meire Munhak da Silva; Jossiana Wilke Faller; Diogo Francisco Rossoni; Jackson Luiz Domareski; Reinaldo Antônio Silva-Sobrinho; Adriana Zilly (Instituto de Estudos em Saúde Coletiva da Universidade Federal do Rio de Janeiro, 2020)
Abstract Background The Brazilian Ministry of Health, by the National Policy on Medication, Ordinance 3916 from October 30th 1998, reinforces the Law of Generics of February 1999 (Law No. 9787 from February 10th, 1999, aiming, among other things, to reduce the prices and make access to medications easier for population). Objective The main objective was to identify the level of knowledge of the population regarding generic drugs. Method Descriptive, quantitative study, with 520 users interviewed in four health care units that implemented the Brazilian Family Health Program. Such units represent four health districts in Foz do Iguaçu, PR, Brazil. Results Most of the interviewed know and/or have heard about generic drugs. For many people, the generic drug represents only a more affordable type of medication. Conclusion The need for health education to clarify the population's questions was found, so they could identify and acquire their medication safely and with confidence.